2018
DOI: 10.1080/21645515.2018.1493326
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward a group B streptococcal vaccine

Abstract: Streptococcus agalactiae (group B Streptococcus, GBS) is a leading cause of severe invasive disease in neonate, elderly, and immunocompromised patients worldwide. Despite recent advances in the diagnosis and intrapartum antibiotic prophylaxis (IAP) of GBS infections, it remains one of the most common causes of neonatal morbidity and mortality, causing serious infections. Furthermore, recent studies reported an increasing number of GBS infections in pregnant women and elderly. Although IAP is effective, it has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 177 publications
(231 reference statements)
1
30
0
1
Order By: Relevance
“…Based on our findings, a protein-alum adjuvant vaccine, which contains the alp family surface proteins (alp1/epsilon, alp2/3, alpha C and Rib), has the potential to prevent up to 87% of maternal colonisation, 99% of adult invasive disease and 93% infant invasive disease (percentages of isolates with at least one of the four protein targets). In addition to the alp protein-based vaccines, the pilus proteins have been proposed as potential vaccine candidates, albeit with conflicting data on whether it has potential as a vaccine candidate [31] , [79] . Our findings require confirmation from ongoing seroepidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our findings, a protein-alum adjuvant vaccine, which contains the alp family surface proteins (alp1/epsilon, alp2/3, alpha C and Rib), has the potential to prevent up to 87% of maternal colonisation, 99% of adult invasive disease and 93% infant invasive disease (percentages of isolates with at least one of the four protein targets). In addition to the alp protein-based vaccines, the pilus proteins have been proposed as potential vaccine candidates, albeit with conflicting data on whether it has potential as a vaccine candidate [31] , [79] . Our findings require confirmation from ongoing seroepidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…Five major clonal complexes in humans (CC1, CC10, CC17, CC19, and CC23) are associated with colonisation and invasiveness of GBS [28] , [29] , [30] . GBS strains can also be classified on the basis of surface proteins, such as Alp family proteins, serine-rich repeat proteins, C5a peptidase, and pilus islands [31] . Proteins such as hvgA, Rib and pilus island proteins have also been associated with invasiveness of GBS strains [32] , [33] , [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of different GBS serotypes may vary in different countries, however, the most common serotypes (Ia, Ib, II, III, IV, and V) are dominant globally, with only Asia reporting a slightly higher proportion of cases due to one additional serotype (VII) (205). The distribution of serotypes responsible for early and late -onset GBS disease also varies, with the most common serotypes being III and Ia (206). Correlates of protection for the different GBS serotypes against the various clinical conditions associated with the pathogen (i.e., colonization, maternal and infant disease) are not precisely defined (207), and these correlates may vary by serotype (207).…”
Section: Group B Streptococcus Vaccinesmentioning
confidence: 99%
“…2 WHO reported that 116 million infants worldwide received three doses of diphtheria-tetanuspertussis vaccine, and about 85% of the world's children received one dose of measles vaccine by their first birthday through routine health services in 2015. 7 Studies for vaccine development have been conducted year by year, 2,[8][9][10] although there has been marked progress in vaccine development, challenges still exist, 8,11 including economic, vaccination for new emerging infectious diseases, and so on. The achievement on vaccine was reflected by scientific studies, 12 particularly in the most cited studies.…”
Section: Introductionmentioning
confidence: 99%